Customer Loyalty Dynamics: The Influence of Halal Certification, Trust, and Brand Preference in the Indonesian Fast Food Industry - Ali; Reinarto, Riko; Wibowo, Mas Wahyu; Permana, Dudi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The COVID-19 pandemic has significantly altered consumer behavior in Indonesia, with a stronger focus on essential needs such as food and beverages. This shift in priorities has been met with a positive response from businesses in the fast-food industry. KFC, one of the most prominent fast-food chains in Indonesia, serves as the context for this study. The research focuses on Indonesian Gen Z consumers who have previously purchased from KFC, with a sample of 180 respondents selected through purposive sampling. The study uses SEM-PLS analysis with Smart-PLS 4.0 software, revealing that Halal Certification, Brand Preference, and Trust have a positive and significant impact on Customer Loyalty. Additionally, Trust and Brand Preference act as mediators in the relationship between Halal Certification and Customer Loyalty, highlighting the importance of these factors in shaping consumer behavior. The findings suggest that halal certification not only influences customer loyalty directly but also strengthens brand preference and trust, which are crucial in fostering long-term loyalty. This is particularly important in the Indonesian market, where ethical and religious considerations are key drivers in consumer decision-making, especially among the younger generation